UJI BERBAGAI DOSIS EKSTRAK KULIT JENGKOL TERHADAP PERTUMBUHAN GULMA Echinochloa cruss-galli (L.) Beauv - Risvan Anwar; Prihanani Prihanani; Rusman Aswardi (University of Prof. Dr. Hazairin, SH, 2013)
This study was aimed to study whether jengkol peel extract could suppress the growth of weed of Echinochloa cuss-galli, and the dose of it that effectively suppress the E. cuss-galli. This research was conducted in Teluk Segara sub district, Bengkulu from Desember 2012 to February 2013. The experimental design used was completely randomized with five replications. Jengkol extract dose treatmen were 0 g (as a control), 100 g, 200 g, 300 g, 400 g, 500 g extract each 250 ml of water. The research concluded that jengkol ekstract affect the growth of E. cuss-galli. Jengkol extract could suppress the growth of E. cuss-galli. The higher dose of extract caused the lower the growth of weeds E. cuss-galli.